A current view on the alcohol-related teratogenic effects during pregnancy. Potential preventive measures - A. Yu. Marianian; A. N. Kalkova (Акушерство, гинекология и репродукция)
Aim: to analyze and summarize the available data of studies aimed at obtaining deeper insight in the field of alcohol-related effects on the course of pregnancy and potential consequences thereof; to study the prevalence of alcohol consumption by women in Russia, as well as potential preventive measures.Materials and Methods. The results of the Russian and foreign studies on the alcohol-related effect on the fetus and pregnancy outcome, published in the international databases Scopus, Web of Science, PubMed/MEDLINE, Cochrane Library, have been analyzed. The search for scientific publications was limited to the period from the years 2012 to 2021. We used search queries in Russian and English ("alcohol", "pregnancy", "prevention", "fetus", "fetal alcohol syndrome").Results. The presented data analysis indicates an extremely negative effect of alcohol on the body of pregnant women, as well as on the health of our future generation. This article proves the importance of the problem, the need for further research on the mechanisms of fetal alcohol syndrome (FAS) and the development of effective prevention measures, potential treatment methods, and assistance for FAS. At present, in Russia there is an acute lack of information on the real extent of the problem with maternal alcohol consumption during pregnancy. Still, no precise data on FAS prevalence in Russia are available.Conclusion. Preventing FAS is an urgent and unexplored issue in Russia. Medical doctors able to conduct pregravid preparation of a married couple while they plan to conceive a healthy child are highly demanded. It is necessary to raise awareness and improve the quality of training for obstetricians and gynecologists in order to identify women with high risk factors for alcohol abuse and childbirth with FAS at early stages of pregnancy management. It is also necessary to identify new or use already identified maternal blood biomarkers to verify excessive alcohol consumption during pregnancy.